Evolution and Implementation of Continuous Testing in Enterprise Software Engineering - Srikanth Kunchaparthy, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Continuous testing has emerged as a critical component in modern enterprise software development, yet organizations face significant challenges in implementing and scaling these practices effectively. This article presents a comprehensive framework for integrating continuous testing within enterprise-scale software development pipelines, addressing the unique challenges of complex, distributed systems. Through this article of real-world implementations and industry best practices, this article outlines a structured approach that encompasses tool selection, infrastructure requirements, and implementation strategies specifically tailored for large-scale applications. The framework considers critical factors such as legacy system integration, regulatory compliance, and cross-team collaboration while providing concrete metrics for measuring success and return on investment. This article findings demonstrate that a well-structured continuous testing approach can reduce deployment cycles by 40% while improving overall software quality and team productivity. This article contributes to the growing body of knowledge on enterprise-scale testing automation and provides actionable insights for organizations transitioning to continuous testing practices.
Keywords: Continuous Testing; Enterprise Software Development; Test Automation; CI/CD Integration; Quality Assurance Metrics